Navigating the academic career : common issues and uncommon strategies - Shaw, Victor N. (Emerald Publishing Limited : Information Age Pub., 2013)
There is an urgent need to provide academic professionals with individual, institutional, and contextual accounts of their careers and career-making endeavors. An individual account makes academicians think about what they do and how they might do it better. An institutional account makes academicians reflect upon the organizational environment in which they function and ponder what they might do to improve it. A contextual account connects academicians and their work to knowledge, the knowledge enterprise, and the larger social structure so that they know and understand the impact they and their career-making efforts have on themselves, academia, and general social processes.This book examines academic careers and career-making activities with respect to their main aspects, milestones, and general pathways. In content, it divides into four identifiable parts. Part I focuses on professional preparation. It examines education, degree, reeducation, job search, and job change. Part II centers on organizational employment. It investigates position, research, teaching, service, and tenure. Part III revolves around professional networking. It looks into publication, conference presentation, application for grants and awards, and membership in academic associations. Part IV rises above specific issues. It explores general career pathways and overall scholarly identity.